Answer:
1 -> d
2 -> c
3 -> g
4 -> b
5 -> a
6 -> i
7 -> h
8 -> e
9 -> j
10 -> f
Step-by-step explanation:
1) (3+7x)(6+2x)
= 18+6x+42x+14x²
=14x²+48x+18
2) (2u³-5u²-7u)(3u³+4u²)
=6u⁶+8u⁵-15u⁵-20u⁴-21u⁴-28u³
=6u⁶-7u⁵-41u⁴-28u³
3) (x+3)(2x²+10x+1)
=2x³+10x²+x+6x²+30x+3
=2x³+16x²+31x+3
4) (-6y²-6y)(-7y²-7y)
=42y⁴+42y³+42y³+42y²
=42y⁴+84y³+42y²
5) (5+x)(2x-10)
=10x-50+2x²-10x
=2x²-50
6) (2k³-4k²-4k)(7k²+2k)
=14k⁵+4k⁴-28k⁴-8k³-28k³-8k²
=14k⁵-24k⁴-36k³-8k²
7) (x-x²)(x²-x)
=x³-x²-x⁴+x³
=-x⁴+2x³-x²
8) (2u³-5u²-7u)(3u³+4u²)
=6u⁶+8u⁵-20u⁴-21u⁴-28u³-21u⁴
=6u⁶+8u⁵-41u⁴-28u³
9) (jk+xy)(7jk+9xy)
=7j²k²+9xyjk+7jkxy+9x²y²
=7j²k²+16xyjk+9x²y²
10) (-2y)(7y³-4y²)
=-14y⁴+8y³